Manufacture of long spars: Laminate design, experimental trials and non-destructive evaluation. (15th April 2023) - Scarth, C.; Chen, Y.; Aza, C.; Rhead, A.T.; Butler, R.
Abstract: Although an enabler of high-rate manufacture, automated forming of components from flat laminates can result in fibre wrinkling. For the first time, fibre length is demonstrated to be a key driver of wrinkling defects when forming a C-spar with a central recess, at industrial length scales. Three such spars, of equal in-plane stiffness, were manufactured using Single Diaphragm Forming. Two contained standard ply angles (0°, 90° or ±45°) including 6 m long 0° fibres but had different stacking sequences, one shown to be formable in short spar trials, the other un-formable. A third spar also had a formable sequence but contained non-standard ply angles (angles other than 0°, 90° or ±45°) so that maximum fibre length was less than 0.6 m. Wrinkles occurred in both standard angle spars but did not occur in the non-standard angle case, demonstrating that use of formable, non-standard angle laminates can reduce scrappage of automatically formed aerospace parts, leading to significant time and cost savings in production.